2015
DOI: 10.1155/2015/596504
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Microbiological Profile of Pathogens in Febrile Neutropenia in Hematological Malignancies: A Single Center Prospective Analysis

Abstract: Background. Febrile neutropenia is the consequence of treatment of hematological disorders. The first-line empirical treatment should cover the prevalent microorganism of the institute. The aim of study was to establish the effectiveness of current practices used at the institution and to review the culture sensitivity pattern of isolated microorganisms. Patients and Methods. Data was recorded and analyzed prospectively for 226 hospitalized patients of febrile neutropenia from January 2011 till December 2013. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
16
4
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 14 publications
5
16
4
1
Order By: Relevance
“…Bacteriological data revealed that Gram-negative infections accounted for 92.3% and E. coli was the most common isolate. This finding was consistent with many other trials which have reported that E. coli is still the most frequently isolated Gramnegative organism in hematological malignancies [7][8][9][10][11]. The antibiotic treatment prior to taking blood cultures may be considered a reason for the lower rates of isolation of bacteria, since half of the E. coli cases among MDI were MDR strains.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Bacteriological data revealed that Gram-negative infections accounted for 92.3% and E. coli was the most common isolate. This finding was consistent with many other trials which have reported that E. coli is still the most frequently isolated Gramnegative organism in hematological malignancies [7][8][9][10][11]. The antibiotic treatment prior to taking blood cultures may be considered a reason for the lower rates of isolation of bacteria, since half of the E. coli cases among MDI were MDR strains.…”
Section: Discussionsupporting
confidence: 90%
“…In the current study, total MDI in IE were 13 (20%) and FN were 4 (10.8%). This rate was slightly lower than in previous studies that have reported microbiological confirmation of BSI in only 15% to 43 % of cases of FN [7][8][9][10]. Bacteriological data revealed that Gram-negative infections accounted for 92.3% and E. coli was the most common isolate.…”
Section: Discussioncontrasting
confidence: 58%
“…Despite a diagnostic focus on bacteremia and concern about resulting clinical sepsis, microbiological confirmation of BSI only occurs in 15% to 35% of cases of FN, and reported in-hospital mortality ranges from 3 to 39% [3, 4, 9]. This wide range is attributable, in part, to the emerging challenge of multi drug-resistant organisms in some populations, particularly the gram-negative bacteria [10].…”
Section: Introductionmentioning
confidence: 99%
“…This study performed on 231 cases of febrile neutropenia from which Staphylococcus aureus could be isolated from 179 (77.4%). On reverse to this work, a study performed by Taj et al (2015) found that Gram negative infections accounted for 68 (85%) and Escherichia coli was the commonest isolate. Gram positive microorganisms were isolated in 12 (15%) cases and most common was S. aureus.…”
Section: Discussionmentioning
confidence: 86%
“…This study reported only one staphylococcus isolate (1%) with constitutive clindamycin resistance; resistant to vancomycin and 12 strains with inducible clindamycin resistance (12%) were resistant to vancomycin. Taj et al (2015) also reported that the commonest Gram positive isolate is S. aureus and 4 cases of MRSA were isolated: all were sensitive to vancomycin; however, 2 cases of vancomycin resistant enterococci (VRE) were documented and were treated successfully with linezolid. In this study, sputum samples represents 26%, pus and urine 18.4 and 18.4% respectively, throat swab 19.4%, blood 17.3% of the clinical samples of cancer patients febrile neutropenia.…”
Section: Discussionmentioning
confidence: 99%